Search Algorithm Optimization In E-Commerce Applications For Better User Experience - Simeramisna, Brenda Sita (Jurnal Komputer Indonesia, 2023)
In the competitive world of e-commerce, user experience is a key factor in attracting and retaining customers. One of the important elements in user experience is the efficiency and accuracy of the search feature. This article discusses the optimization of search algorithms in e-commerce applications to improve user experience. This research explores various optimization techniques, such as search personalization, the use of machine learning algorithms, and user behavior analysis. Through experiments and data analysis, it is found that optimized search algorithms can significantly improve user satisfaction, speed up the search process, and ultimately, increase sales conversion. The results of this study show that integrating advanced technologies in search algorithms is an effective strategy in developing competitive e-commerce applications.